2022
DOI: 10.1038/s41467-022-31953-6
|View full text |Cite
|
Sign up to set email alerts
|

Competing electronic states emerging on polar surfaces

Abstract: Excess charge on polar surfaces of ionic compounds is commonly described by the two-dimensional electron gas (2DEG) model, a homogeneous distribution of charge, spatially-confined in a few atomic layers. Here, by combining scanning probe microscopy with density functional theory calculations, we show that excess charge on the polar TaO2 termination of KTaO3(001) forms more complex electronic states with different degrees of spatial and electronic localization: charge density waves (CDW) coexist with strongly-l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The polar nature of the KTO slab may explain the origin of the conducting system, similar to that of LaAlO 3 |SrTiO 3 interface [8]. Alternatively, an uncompensated charge on the KTO surface may lead to complex electronic states like charge density waves coexisting with strongly-localized electron polarons and bipolarons [18]. Superconductivity may reportedly be induced on the surface of an insulating crystal of KTO [19].…”
Section: Introductionmentioning
confidence: 98%
“…The polar nature of the KTO slab may explain the origin of the conducting system, similar to that of LaAlO 3 |SrTiO 3 interface [8]. Alternatively, an uncompensated charge on the KTO surface may lead to complex electronic states like charge density waves coexisting with strongly-localized electron polarons and bipolarons [18]. Superconductivity may reportedly be induced on the surface of an insulating crystal of KTO [19].…”
Section: Introductionmentioning
confidence: 98%
“…Additionally, the surface termination can influence polar distortions in LaNiO 3 thin films, determined from the analysis crystal truncation rods (CTR) measured by synchrotron x-ray diffraction, thereby altering the electronic conduction 13 . Other experimental observations have revealed different phases at polar surfaces, such as polarization-controlled surface reconstruction in a Pb(Zr 0.2 Ti 0.8 )O 3 film 11 and competing electronic states, e.g., charge-density waves and localized electron polarons, at a TaO 2 -terminated polar surface in a KTaO 3 film 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Capping with an insulating LaAlO 3 layer 17 or changing the surface termination 13 can reduce or eliminate the polar distortion, and thus recover the metallic conductivity of the LaNiO 3 film again. Furthermore, the excess charges on the polar surfaces lead to the emergence of different electronic states such as charge-density waves, localized electron polarons 18 , and two-dimensional electron gas (2DEG) 19 . Additionally, surface polarization can effectively boost electro- and photocatalytic performance by tuning the adsorption intensity and charge separation at catalyst surfaces 10 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a small polaron is usually confined with a range on the order of the lattice constant, which forms a narrow localized in-gap state (about 1 eV below the Fermi level) and shows insulating behavior with slow hopping mobility. Intriguingly, many recent studies have reported that free-like electrons even with high mobility can coexist with small polarons in materials, [13][14][15][16][17][18][19] which seems to run counter to the strongly localized nature of small polarons. Furthermore, the underlying mechanism of the coexistence of delocalized electrons and localized polarons remains largely underexplored.…”
Section: Introductionmentioning
confidence: 99%